ANALYSIS OF ABILITY AND DETERMINANT FACTORS AT THE FLOWERING STAGE - Erma Lisa; Syafi’i, Wan Syafi’i (Universitas Lancang Kuning, 2025)
In every higher plant, there will be a change from vegetative to generative. In this change, a series of new structures will be formed, namely flowers. Flowers are an expression of genes that were not previously expressed. The flowering stage is one of the stages of the development phase that needs to be considered in plants. Therefore, it is necessary to understand the factors that influence the flowering stage. This study aims to determine the factors that influence flowering. The method used in this article is through journal reviews. The number of journal articles reviewed and analyzed was 15 journal articles that had relevant topics. Then the results of the study are presented in descriptive form and presented in a table. Based on the results of the literature review, it is known that there are many factors that influence the flowering stage, including temperature and humidity, paclobutrazol, the influence of auxin and gibberellin growth regulators, types of containers and fertilizer concentrations, photoperiods, various types of fertilizers, eco enzymes and pinching.